ANALISIS KORELASI PREDIKSI PERUBAHAN GENANGAN ROB TERHADAP PREDIKSI PERUBAHAN ZONA NILAI TANAH DI KECAMATAN SEMARANG UTARA - Ikhsan, Edi; Suprayogi, Andri; ., Hani'ah (Departement Teknik Geodesi Universitas Diponegoro, 2012)
In the coastal region geomorphology process on going of a complex so that the is a dynamic system. Physical processes and human intervention to separate the pressure on coastal areas. Semarang coastal area including northern Semarang district has a sloping topography with a slope of 0-2%. With a sloping topography, the city of Semarang is very vulnerable to the impact caused by rising sea levels. One thing that often happens is that the flood tide (rob). If sea levels continue to rise, it can result in increasing the extent of inundation rob a place in the city of Semarang. So it can be assumed that the pool would rob correlated to the value of the land. This study used the mean sea level data years 1985-2010 of the final project Catur Julianto in 2011, data reduction in the face of the land in Semarang, data from the spot height semarang topographic maps, data NJOP per meter of land in the district north Semarang years 1994-2011, and map of the zone land value in 2011. This research will rob prediction maps generated in 2015, 2020, and 2025 in Semarang on Safe inundation scenarios, HHWL, MSL, and LLWL, rob our predictions in districts north Semarang zone land value, the price of land according to land value zone code 2015, 2020, and 2025, and the correlation of changes rob a pool of predictions to changes in the soil zone. The results showed that the pool of rob in the city of Semarang each year will increase. The main cause is the decline in the face of earth is happening in the city of Semarang. While the value of land in areas prone to rob it tends to go up from year to year. 2015, 2020, and 2025 is predicted to be at a maximum price of AU in the village code Dadapasari and minimum prices are on the AW code Lor village stage. While the correlation of changes in the scenario inundation zone rob to changes in the value of land in an area safe from inundation rob predicted by 94%, were flooded when HHWL by 82%, and were inundated when the MSL by 73%.